2017
DOI: 10.3389/fmars.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

The Grand Challenges in Researching Marine Noise Pollution from Vessels: A Horizon Scan for 2017

Abstract: Chronic anthropogenic underwater noise, such as vessel noise, is now recognized as a world-wide problem. Marine noise from vessels, ranging from super tankers to small motorboats is increasingly recognized as being both a persistent and pervasive pollutant. Furthermore, due to its spatial and temporal variability, vessel noise pollution represents a particular challenge for marine conservation, management, and planning. This paper presents the outputs of a horizon scanning exercise that brought together a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Smaller vessels, particularly recreational boats, can present a substantial threat in the marine environment in some areas as an unregulated noise source with higher interaction rates with marine animals than any other source (Correa et al, 2019). Furthermore, the sheer volume of recreational boat traffic can dilute the mitigating effect of their transient nature (McWhinnie et al, 2017). Assessing the effects of these vessel movements on the marine environment has become a management challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller vessels, particularly recreational boats, can present a substantial threat in the marine environment in some areas as an unregulated noise source with higher interaction rates with marine animals than any other source (Correa et al, 2019). Furthermore, the sheer volume of recreational boat traffic can dilute the mitigating effect of their transient nature (McWhinnie et al, 2017). Assessing the effects of these vessel movements on the marine environment has become a management challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant in highly productive waters that are near major port‐cities, such as the Salish Sea near Vancouver (Cominelli et al, 2018; Joy et al, 2019), the Pearl River Estuary near Hong Kong (Pine et al, 2017; Sims et al, 2012) and the Hauraki Gulf near Auckland (Pine et al, 2016; Putland et al, 2018). A common threat facing these productive waters is increasing levels of vessel noise from an increasing volume of commercial and recreational marine traffic (Dolman & Jasny, 2015; Farcas et al, 2020; Hildebrand, 2009; Luís et al, 2014; McWhinnie et al, 2017; Pine et al, 2016; Simmonds et al, 2014; Weilgart, 2007). For example, Auckland, which is New Zealand's largest city, is located within the centre of the Hauraki Gulf Marine Park (HGMP), an area of 4000 km 2 with outstanding marine biodiversity including >700 species of marine intertidal invertebrates, >80 species of fish and 25 species of marine mammals, at least six of which are resident (Hauraki Gulf Forum, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development and diversification of human activities, especially in coastal waters, have increased the exposure of dolphins to a variety of anthropogenic disturbances ( Sini et al, 2005 ). Industrial and recreational vessel traffic is one of the main threats and is predicted to rise ( Erbe et al, 2019 ; McCarthy, 2004 ; McWhinnie et al, 2017 ; O’Connor et al, 2009 ). In the presence of vessels, dolphins have shown changes in habitat use ( Lusseau, 2005 ; McCarthy, 2004 ), group composition and cohesion ( Bejder et al, 2006 ; Miller, Solangi & Kuczaj, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…One example in this study was noise pollution; when an in-depth evaluation for a specific noise source is required, a Delphi exercise (or other approach) with a more specific focus is needed. An example is the study by McWinnie et al [17] who investigated marine noise pollution from vessels in Canada and identified priority information needs to inform new research and address policy needs through an iterative Delphi style process and workshop.…”
Section: Discussionmentioning
confidence: 99%